2022
DOI: 10.1186/s12866-022-02478-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of floor- and net-rearing systems on intestinal growth and microbial diversity in the ceca of ducks

Abstract: Background Rearing systems can affect livestock production directly, but whether they have effects on intestinal growth states and ceca microorganisms in ducks is largely unclear. The current study used Nonghua ducks to estimate the effects of rearing systems on the intestines by evaluating differences in intestinal growth indices and cecal microorganisms between ducks in the floor-rearing system (FRS) and net-rearing system (NRS). Results The valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…The rearing system affects the gastrointestinal microbiota, which, in turn, affects the production performance and health of animals. Intriguingly, our taxonomic classification showed that Firmicutes, Bacteroidetes, Actinobacteria, and Deferribacteres were the most abundant bacteria in the cecum, which is in agreement with previous studies on chickens and ducks ( Onrust et al, 2015 ; Xiao et al, 2017 ; Wang et al, 2021 ; Chen et al, 2022 ). Results of 16S rRNA sequencing show that human and mouse cecal bacteria were mainly composed of Bacteroidetes and Firmicutes, while Bacteroidetes and Firmicutes in the pig cecal digestive tract were the main phyla from farrow to finish ( Brücher and Jamall, 2019 ; Yue et al, 2019 ; Quan et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…The rearing system affects the gastrointestinal microbiota, which, in turn, affects the production performance and health of animals. Intriguingly, our taxonomic classification showed that Firmicutes, Bacteroidetes, Actinobacteria, and Deferribacteres were the most abundant bacteria in the cecum, which is in agreement with previous studies on chickens and ducks ( Onrust et al, 2015 ; Xiao et al, 2017 ; Wang et al, 2021 ; Chen et al, 2022 ). Results of 16S rRNA sequencing show that human and mouse cecal bacteria were mainly composed of Bacteroidetes and Firmicutes, while Bacteroidetes and Firmicutes in the pig cecal digestive tract were the main phyla from farrow to finish ( Brücher and Jamall, 2019 ; Yue et al, 2019 ; Quan et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, dryland rearing on netting floors has been noted to enhance the intestinal immunity and reduce the mortality rate ( 2 ). Studies on Nonghua ducks demonstrated that floor rearing individuals had significantly higher relative weight, relative length and relative weight/relative length ratios of the ileum compared to net rearing individuals ( 16 ). In geese, previous research has indicated that cage rearing geese exhibited a higher villus height/crypt depth ratio, suggesting the potential benefits of cage rearing in enhancing geese resistance against diseases and toxins ( 17 ).…”
Section: Introductionmentioning
confidence: 99%